Feasibility of a Dance PaRticipation intervention for Extremely prEterm children with Motor Impairment at prEschool age (Dance PREEMIE). (December 2021) - Cameron, Kate L.; Allison, Kim; McGinley, Jennifer L.; Fini, Natalie A.; Cheong, Jeanie L.Y.; Spittle, Alicia J.
Abstract: Background: Physical activity (PA) participation provides opportunities for preschool-age children to improve motor skills. This is especially important for children born extremely preterm (EP) or extremely low birthweight (ELBW) who are at greater risk of motor impairment, and are participating less frequently in PA, compared with children born at term. There is limited evidence on improving PA participation for this population. Methods: This case series design study evaluated the feasibility of a Dance PaRticipation intervention for Extremely prEterm children with Motor Impairment at prEschool age (Dance PREEMIE), a community-based dance class intervention aiming to improve PA participation. Children born EP/ELBW with motor impairment were recruited at 3 years' corrected age. Dance teachers were recruited from community dance schools and provided with study-specific training. Intervention feasibility was assessed using; recruitment capability, class attendance, child involvement and enjoyment, teacher self-efficacy, and implementation fidelity. Results: Ten children and seven dance teachers were recruited. Most children ( n  = 7) attended >75% of classes. Children enjoyed the classes and were mostly 'somewhat-very' or 'very' involved. Teachers reported improved self-efficacy for teaching dance to children with motor impairment after attending the training day. Conclusion: Further research is warranted to evaluate the efficacy of Dance PREEMIE in larger samples. Highlights: Physical activity participation may benefit children born extremely preterm. Dance PREEMIE is a community-based intervention for children with motor impairment. Dance PREEMIE was fun, engaging, and well-attended by participating families. Dance teachers attended Dance PREEMIE training before facilitating intervention. Training improved self-efficacy for teaching children with motor impairment.